The Roles of Dopamine Transport Inhibition and Dopamine Release Facilitation in Wake Enhancement and Rebound Hypersomnolence Induced by Dopaminergic Agents - Gruner, John A. (Associated Professional Sleep Societies, LLC, 2009)
STUDY OBJECTIVE: Rebound hypersomnolence (RHS: increased sleep following increased wake) is a limiting side-effect of many wake-promoting agents. In particular, RHS in the first few hours following wake appears to be associated with dopamine (DA)-releasing agents, e.g., amphetamine, but whether it can also be produced by DA transporter (DAT) inhibition alone is unknown. In these studies, DA-releasing and DAT-inhibiting agents and their interaction were systematically examined for their ability to increase wake and induce RHS. DESIGN: Chronically implanted rats were evaluated in a blinded, pseudo-randomized design. PARTICIPANTS: 237 rats were used in these studies with 1 week between repeat tests. INTERVENTIONS: Animals were habituated overnight and dosed the next day, 5 h after lights on, with test agents. MEASUREMENTS AND RESULTS: Sleep/wake activity and RHS were evaluated using EEG/EMG recording up to 22 h post dosing. In vitro dopamine release was evaluated in rat synaptosomes. At doses that produced equal increases in wake, DA-releasing (amphetamine, methamphetamine, phentermine) and several DAT-inhibiting agents (cocaine, bupropion, and methylphenidate) produced RHS during the first few hours after the onset of sleep recovery. However, other DAT-inhibiting agents (mazindol, nomifensine, GBR-12909, and GBR-12935) did not produce RHS. Combination treatment with amphetamine and nomifensine produced waking activity greater than the sum of their individual activities alone while ameliorating the amphetamine-like RHS. In rat synaptosomes, nomifensine reduced the potency of amphetamine to induce DA release ∼270-fold, potentially explaining its action in ameliorating amphetamine-induced RHS. CONCLUSIONS: All DA releasing agents tested, and some DAT-inhibiting agents, produced RHS at equal wake-promoting doses. Thus amphetamine-like DA release appears sufficient for inducing RHS, but additional properties (pharmacologic and/or pharmacokinetic) evidently underlie RHS of other DAT inhibitors. Enhancing wake while mitigating RHS can be achieved by combining DAT-inhibiting and DA-releasing agents. CITATION: Gruner JA; Marcy VR; LinYG; Bozyczko-Coyne D; Marino MJ; Gasior M. The roles of dopamine transport inhibition and dopamine release facilitation in wake enhancement and rebound hypersomnolence induced by dopaminergic agents. SLEEP 2009;32(11):1425-1438.